Diffuse Large B-cell Lymphomas of Immunoblastic Type Are a Major Reservoir for MYC-IGH Translocations. (January 2015) - Horn, Heike; Staiger, Annette M.; Vöhringer, Matthias; Hay, Ulrich; Campo, Elias; Rosenwald, Andreas; Ott, German; Ott, M. Michaela
Abstract : The immunoblastic variant of diffuse large B-cell lymphoma (IB-DLBCL) has recently been recognized as an aggressive lymphoma type with inferior prognosis as compared with other DLBCL variants. At the same time, the presence of MYC rearrangements in DLBCL has been shown to indicate shorter survival in R-CHOP-treated patients. In this study, we investigated the occurrence of MYC gene rearrangements in IB-DLBCL versus non-IB-DLBCL in a large series. Using fluorescence in situ hybridization with an MYC break-apart and MYC - IGH fusion probe, we found that 13/39 evaluable IB-DLBCLs (33%) harbor translocations involving MYC, in contrast with only 5/68 (7%) in the non-IB-DLBCL group ( P <0.01). The immunoglobulin heavy chain gene ( IGH ) was the translocation partner in all rearrangements (100%) involving MYC in IB-DLBCL, which is in contrast to what has been reported for DLBCL in the literature (50% to 70%). Moreover, MYC rearrangements occurred as the sole translocation in the majority of cases (77%), whereas across all DLBCLs the majority of MYC -rearranged cases carry additional rearrangements of either BCL2 and/or BCL6 genes (between 58% and 83% of cases). Finally, MYC -rearranged IB-DLBCLs were CD10 positive in 62% (8/13), whereas this was an uncommon feature in MYC germline IB-DLBCLs (15%). In conclusion, IB-DLBCLs are genetically characterized by frequent MYC - IGH translocations that often occur without additional BCL2 and/or BCL6 translocations. The activation of MYC, therefore, may be an important pathogenetic feature in IB-DLBCL.